KARAKTERISTIK DAN POTENSI PEMANFAATAN ASAP CAIR KAYU TREMA, NANI, MERBAU, MATOA, DAN KAYU MALAS - Sri Komarayati; Gusmailina; Lisna Efiyanti (BRIN Publishing, 2018)
Wood is potential biomass with various benefits such as is utilizing them for liquid smoke raw material. Consequently, research on liquid smoke by pyrolysis should be conducted intensively to gain necessary information on the active content and utilization of the liquid smoke. This research is aimed to determine characteristics and potential utilization of liquid smoke made from trema, nani, merbau, matoa and malas wood. Research was conducted by pyrolysis process at 500°C for 5 hours and the liquid smoke was collected in container for analyzes. Analysis of liquid smoke characteristics included pH, specific gravity, acetic acid, phenol and other chemical component content using py-GCMS. The result showed that the pH ranged from 2.68 to 4.34, specific gravity ranged from 0.83 to 1.04, acetate 0.65–13.09%, and phenol content 0.19–2.50%. GCMS analysis showed chemical component diversity and its main component as identity of specific liquid smoke from five wood species confirmed were acetic acid (acetic acid, ethylic acid), phenolic (phenol, 2,6-dimethoxy (CAS) 2,6-dimethoxyphenol), and carbamic acid. The chemical component of liquid smoke is expected to be applied in wide variety of products based on product’s perspective, objectives and product targets that would be achieved.